Observation of the molecular response to light upon photoexcitation - Haiwang Yong (Nature Portfolio, 2020)
Photoabsorption is a fundamental process that leads to changes in the electron density in matter. Here, the authors show a direct measurement of the distribution of electron density when a cyclohexadine molecule is excited by pulsed UV radiation and probed by a time delayed X-ray pulse generated at LCLS.